2004
DOI: 10.1074/jbc.m409449200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the γ-Aminobutyric Acid Transporter-1 Is Driven by an Interplay of Polar and Hydrophobic Interactions in Transmembrane Helix II

Abstract: The available evidence indicates that members of the neurotransmitter:sodium symporter family form constitutive oligomers. Their second transmembrane helix (TM2) contains a leucine heptad repeat proposed to be involved in oligomerization. In artificial transmembrane segments, interhelical interactions are stabilized by polar residues. We searched for these hydrogen bond donors in TM2 by mutating the five polar residues in TM2 of the ␥-aminobutyric acid transporter-1 (GAT1). We tested the ability of the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…It is also evident that the COOH terminus of DAT is required to stabilize the overall conformation, because several mutations within the COOH terminus disrupt ligand binding (30). In contrast, whereas truncation of the COOH terminus causes retention of GAT1 in the endoplasmic reticulum, it does not impair its ability to translocate substrate or bind inhibitors in vesicular uptake assays (31). Similarly, if GAT1-RL/AS reached the cell surface, the mutated transporter supported substrate influx with an affinity comparable with the wild type, whereas the reduction in V max was accounted for the reduction in cell surface levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is also evident that the COOH terminus of DAT is required to stabilize the overall conformation, because several mutations within the COOH terminus disrupt ligand binding (30). In contrast, whereas truncation of the COOH terminus causes retention of GAT1 in the endoplasmic reticulum, it does not impair its ability to translocate substrate or bind inhibitors in vesicular uptake assays (31). Similarly, if GAT1-RL/AS reached the cell surface, the mutated transporter supported substrate influx with an affinity comparable with the wild type, whereas the reduction in V max was accounted for the reduction in cell surface levels.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies have indicated (Biebermann et al 2005) that MCT8 occurs as dimers comprising two interacting protomers, or, presumably, as higher order complexes such as tetramers (Visser et al 2009). In support of this, other members of the MFS have also been reported to form oligomers, including the glycine transporter (Bartholomaus et al 2008), organic cation transporter 1 (Keller et al 2011), g-amino butyric acid transporter 1 (Korkhov et al 2004), multidrugtransporter EmrD (Yin et al 2006), dopamine transporter (Hastrup et al 2001), and serotonin transporter (Kilic & Rudnick 2000). Higher-order complexes can be functionally relevant such as those found for amphetamine transporters, for which influx and efflux occurs via separate but interacting transporter protomers (Seidel et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the amino acids from positions 267 to 360 (putative TMH4-6) are not involved in MCT8 protomer contacts (Visser et al 2009). However, several contact regions for membrane-spanning transporter oligomers have already been reported (oligomerization is inhibited by mutation): the bacterial Ca 2C /H C antiporter (Ridilla et al 2012) -contacts at TMH2 and TMH6; the Na C /H C antiporter NhaA (Gerchman et al 2001) -loop transition on the cytoplasmatic side of helix 8; the dopamine transporter (Hastrup et al 2003) -at the extracellular end of TMH6; the g-amino-butyric acid transporter 1 -at TMH2 (Korkhov et al 2004); and the glycine transporter 2 (GlyT2) -extracellular transition of TMH6. Very recently, TMH2 has been identified as a crucial dimerization interface of the bacterial sweet transporter (Xu et al 2014).…”
Section: Transporter Oligomers and Structure-function Relationshipsmentioning
confidence: 99%
“…Figure 10 also shows that the reducing agent DTT (12 mM), after treatment with 0.2 mM CuPh, significantly restored the activity of the K102C/D338C mutant. Recent studies have indicated that members of the NSS family form constitutive oligomers (12,13,15,17,19,20,31,32), although the physiological meaning of this process is still under investigation (17,25,33,35,37). Since KAAT1 belongs to the NSS family, we also considered the hypothesis that CuPh may actually cause the creation of a disulfide bond between two cysteines in different subunits of a KAAT1 homo-oligomer.…”
Section: Amino Acid Uptake When Expressed In Xenopus Laevismentioning
confidence: 99%